Molecular basis for cellular retinoic acid-binding protein 1 in modulating CaMKII activation - Nhieu, Jennifer; Miller, Michelle C.; Lerdall, Thomas A.; Mayo, Kevin H.; Wei, Li-Na (Frontiers in Molecular Biosciences, 2023)
Cellular retinoic acid (RA) binding protein 1 (CRABP1) is a highly conserved protein comprised of an anti-parallel, beta-barrel and a helix-turn-helix segment outside this barrel. Functionally, CRABP1 is thought to bind and sequester cytosolic RA. Recently, CRABP1 has been established as a major mediator of rapid, non-genomic activity of RA in the cytosol, referred to as "non-canonical" activity.Previously we have reported that CRABP1 interacts with and dampens the activation of Ca 2+- calmodulin activated kinase 2 (CaMKII), a major effector of calcium signaling. Through biophysical, molecular, and cellular assays, we herein elucidate the molecular and structural mechanism underlying the action of CRABP1 in dampening CaMKII activation. We identify an interaction surface on CRABP1 for CaMKII binding, located on the beta-sheet surface of the barrel, and an allosteric region within the helix segment outside the barrel, both are important for interacting with CaMKII. Molecular studies reveal that CRABP1 preferentially associates with the inactive form of CaMKII, thereby dampening CaMKII activation. Alanine mutagenesis of residues implicates in CaMKII interaction result in either a loss of this preference, or a shift of CRABP1 from associating with the inactive This is a provisional file, not the final typeset article CaMKII to associating with the active CaMKII, which corresponds to changes in CRABP1's effect in modulating CaMKII activation. This is the first study to elucidate the molecular and structural bases for CRABP1's function in modulating CaMKII activation. The results further shed insights into CRABP1's functional role involved in multiple signaling pathways, as well as its extremely high sequence conservation across species and over evolution.